Craving for exercise due to the disruption of daily routine by an earthquake - İsmail İlbak; Ahmet Yasuntimur; Stefan Stojanovic; Serkan Düz; Łukasz Rydzik; Ladislav Cepicka (Frontiers in Sports and Active Living)
ObjectivesThe research aimed to examine exercise cravings that arise from the disruption of daily routine resulting from the earthquake and the consequent mandatory absence from exercising at fitness centers.Study designThis study utilized the phenomenological design through qualitative research methods.MethodsThe research sample comprises six individuals aged between 22 and 29 years. They were selected using the criterion sampling method. Data was collected through semi-structured interviews, and thematic analysis was used to analyze the data.ResultsTwo different types of cravings were identified. The first type is related to exercise addiction, while the second type is related to anxiety-induced cravings.ConclusionsExercise craving manifests in two ways. The first type originates from exercise addiction, emerging when an individual with exercise addiction experiences a lack of exercise. With a more clinical dimension, the second type arises from the inability to engage in training for uncontrollable reasons.